2015
DOI: 10.3122/jabfm.2015.03.140248
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Action: The Impact of an Asthma Action Plan Decision Support Tool Integrated into an Electronic Health Record (EHR) at a Large Health Care System

Abstract: Introduction: Asthma is a chronic airway disease that can be difficult to manage, resulting in poor outcomes and high costs. Asthma action plans assist patients with self-management, but provider compliance with this recommendation is limited in part because of guideline complexity. This project aimed to embed an electronic asthma action plan decision support tool (eAAP) into the medical record to streamline evidence-based guidelines for providers at the point of care, create individualized patient handouts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 34 publications
(28 reference statements)
1
45
0
1
Order By: Relevance
“…We have demonstrated a sustained improvement in the provision of AAPs from 17.9% in 2007 to 71.9% overall, and 85.9% for those discharged with a diagnosis of asthma in 2014–2015. These results are consistent with the use of eAAPs that have been described in other studies and, as well as improved documented provision of an AAP, evaluations have shown an association between eAAP receipt and significant reductions in paediatric asthma exacerbations, including 33% lower odds of requiring oral steroids ( P < 0.001), compared with controls . In addition, the electronic sharing of the AAP has the potential to increase efficiency and enhance effective communication among health‐care providers, families and schools .…”
Section: Discussionsupporting
confidence: 89%
“…We have demonstrated a sustained improvement in the provision of AAPs from 17.9% in 2007 to 71.9% overall, and 85.9% for those discharged with a diagnosis of asthma in 2014–2015. These results are consistent with the use of eAAPs that have been described in other studies and, as well as improved documented provision of an AAP, evaluations have shown an association between eAAP receipt and significant reductions in paediatric asthma exacerbations, including 33% lower odds of requiring oral steroids ( P < 0.001), compared with controls . In addition, the electronic sharing of the AAP has the potential to increase efficiency and enhance effective communication among health‐care providers, families and schools .…”
Section: Discussionsupporting
confidence: 89%
“…School nurse involvement in asthma care coordination has resulted in improvements in health care use, school attendance, medication adherence, and quality of life. 3,4,6,7 School nurses are uniquely positioned to provide direct care, adherence counseling, and education for asthmatic patients. 8 They can review and reinforce proper inhaler technique and usually have the most recorded data of quick-relief medication use—one of the hallmarks of asthma control.…”
Section: Componentmentioning
confidence: 99%
“…[71] The breadth of computerized decision support efforts to date in the EHR is beyond scope for this review, but it is important to highlight efforts in the domain of pediatric asthma. Prior asthma-related CDS includes aids for diagnosis of clinical deterioration through patient electronic self-report,[72] providing evidence based guidelines on asthma action plans at point of care,[73, 74] and asthma self-management applications built for mobile devices. [75] A Cochrane review of the latter category in 2013 demonstrated insufficient evidence regarding integration of mobile device-enabled asthma self-management applications into the clinical workflow.…”
Section: The Role Of Prediction Rules In Clinical Decision-supportmentioning
confidence: 99%